Infection-Triggered Antiphospholipid Syndrome: A Critical Overview - Smiyan S; Kuzmina G; Garmish O; Komorovsky R (Open Access Rheumatology: Research and Reviews)
Svitlana Smiyan,1 Ganna Kuzmina,2 Olena Garmish,3 Roman Komorovsky1 1Department of Internal Medicine II, Ivan Horbachevsky Ternopil National Medical University, Ternopil, Ukraine; 2Department of Therapy, Cardiology and Family Medicine, Faculty of Postgraduate Education, Dnipro State Medical University, Dnipro, Ukraine; 3King’s College Hospital London, Dubai, United Arab EmiratesCorrespondence: Roman Komorovsky, Department of Internal Medicine II, Ivan Horbachevsky Ternopil National Medical University, 1, Maidan Voli, Ternopil, 46001, Ukraine, Email komorovsky@tdmu.edu.uaAbstract: Antiphospholipid syndrome (APS) is a complex multisystem disorder traditionally classified into primary forms and those associated with autoimmune diseases. However, infection-induced APS is gaining attention as a distinct subset due to the increasing recognition of thrombotic complications occurring in the context of viral or bacterial infections. Despite its clinical relevance, this phenomenon remains poorly characterized. This narrative review synthesizes current knowledge on the pathogenesis, clinical manifestations, and diagnostic challenges of infection-induced APS. A literature search was conducted in the Medline and PubMed databases for English-language articles published between 2014 and May 2025. Of the identified publications, 35 were selected for detailed analysis. Evidence supports a multifaceted relationship between infections and APS, with proposed mechanisms including molecular mimicry, Toll-like receptor activation, generation of non-pathogenic antiphospholipid antibodies (aPL), impaired immune complex clearance, neutrophil extracellular trap formation, direct endothelial damage, and the “second hit” hypothesis. Clinical presentations are diverse, ranging from mild, transient symptoms to severe thrombotic events, and often complicate the distinction between true APS and transient aPL positivity secondary to infection. Diagnostic difficulties are compounded by the fluctuating presence of aPL and the overlap of infection-related symptoms with APS criteria. Currently, there are no standardised criteria for infection-induced APS, underscoring the need for definitions that reflect its temporal dynamics and immunological heterogeneity.Keywords: antiphospholipid syndrome, antiphospholipid antibodies, infections, autoimmunity, diagnosis